SMART WATER PUMP DESIGN USING DECISION TREE FOR IOT-BASED AUTOMATIC FRUIT PLANT IRRIGATION - Figur Muhammad; Ramdana Ramdana (Program Studi Teknik Informatika Universitas Khairun, 2025)
The continuous growth of the population each year increases the demand for adequate food supplies, while land for cultivation is becoming more limited. One solution to this issue is the technique of growing fruit in pots (tabulampot). Irrigating potted plants is a crucial maintenance stage, where deficit irrigation can help manage fruit quality. However, manual watering by farmers is time-consuming and labor-intensive, necessitating an automation system. This research aims to design and build a smart water pump system based on the Internet of Things (IoT) using a Decision Tree algorithm to monitor and irrigate potted fruit plants. The designed system can irrigate plants based on predetermined times and soil moisture conditions. Utilizing IoT technology, this system can be accessed and controlled via smartphone. The research results indicate that the system operates automatically, with the ability to monitor soil moisture and irrigate based on real-time sensor data. The implementation of this system is expected to enhance the efficiency of potted plant care and reduce farmers' workload.